Exploring inter-organizational relationships in automotive component remanufacturing - Sebastian Lind; David Olsson; Erik Sundin (Journal of Remanufacturing, 2014)
One of the industry sectors with the longest history in remanufacturing is the automotive industry. Remanufactured parts include brake calipers, engines, servo pumps and alternators. A big challenge for automotive component remanufacturers is to achieve a steady flow of cores (parts that are used for remanufacturing). This flow could be secured by making agreements with core suppliers, such as an original equipment manufacturer (OEM), a core broker or another actor in the market. The remanufacturer can also choose to collect the cores without closer collaboration with the core suppliers. One crucial aspect in choosing how to collect the cores is that it has to be lucrative. The aim of this paper is to explore how remanufacturers manage their inter-organizational relationships in the closed-loop supply chain. A case study was conducted within the European research project 'CAN-REMAN', and empirical data was collected from six participating companies within the project, all European small and medium-sized (SME) remanufacturers of automotive components. These companies were investigated, and their relationships, defined in earlier research with core suppliers, were evaluated. A key finding of the research is that the most problematic parameter with supplier relationships is to receive the ordered quantity of cores from the supplier. This parameter is continually ranked as one of the most important, and the participating companies also claim to have problems with it. A successful relationship and take-back system was pointed out by one of the companies to never be the owner of the actual cores, and only perform the remanufacturing activity (service) for an OEM. This new relationship, called reman-contract, is where the OEM owns the core and the remanufacturer just performs remanufacturing including some sorting and storing. It was found that with this kind of relationship, the ordered quantity of cores was fulfilled to a higher degree, and thus the challenge of achieving a steady flow of cores was met.
Keywords: 650; Reverse logistics; Reverse supply chain; Remanufacturing; Automotive; SME; Inter-organizational; CAN-REMAN